2022
DOI: 10.48550/arxiv.2204.01585
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Universality of Langevin Diffusion for Private Euclidean (Convex) Optimization

Abstract: In this paper we revisit the problem of differentially private empirical risk minimization (DP-ERM) and differentially private stochastic convex optimization (DP-SCO). We show that a well-studied continuous time algorithm from statistical physics, called Langevin diffusion (LD), simultaneously provides optimal privacy/utility trade-offs for both DP-ERM and DP-SCO, under ε-DP, and (ε, δ)-DP. Using the uniform stability properties of LD, we provide the optimal excess population risk guarantee for 2 -Lipschitz co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Recently, [21] gave better privacy bounds for such a regularized exponential mechanism, and designed an efficient sampler based only on function evaluation. Also, [20] showed that the continuous Langevin diffusion has optimal utility bounds for various private optimization problems.…”
Section: Other Related Workmentioning
confidence: 99%
“…Recently, [21] gave better privacy bounds for such a regularized exponential mechanism, and designed an efficient sampler based only on function evaluation. Also, [20] showed that the continuous Langevin diffusion has optimal utility bounds for various private optimization problems.…”
Section: Other Related Workmentioning
confidence: 99%